Berbamine attenuates hind limb ischemia-reperfusion injury by eliminating lipid ROS and inhibiting p65 nuclear translocation - Zheng, Lei; Zhao, Biao; Ji, Run; Zhang, Zhenxi; Liu, Yutong; Zhao, Xiaoqi; Cai, Jing; Qiao, Tong (Frontiers in Pharmacology, 2025)
This research aims to explore whether Berbamine (BBM) can mitigate tissue damage in mice resulting from hind limb muscle ischemia-reperfusion by scavenging lipid ROS and inhibiting p65 nuclear translocation. The hind limb ischemia-reperfusion (IR) injury model in mice was employed. Forty-eight mice (n = 12 per group) were randomly allocated into four groups: Sham group, IR group, IR + BBM (20 mg/kg) group, and IR + BBM (50 mg/kg) group. We observed that BBM pretreatment shielded against muscle damage and diminished levels of cell apoptosis compared to the control group. The mechanism likely involves reducing the movement of p65 into the nucleus and lessening the build-up of lipid ROS in muscle tissue. This action helps to decrease the release of substances that cause inflammation, ultimately reducing the inflammation in tissues that occurs as a result of hind limb IR. Our findings suggest that BBM has a protective impact on hindlimb ischemia-reperfusion injury, potentially due to its capacity to eliminate tissue lipid ROS and prevent p65 nuclear translocation.